KONSELING INDIVIDU DENGAN PENDEKATAN COGNITIVE BEHAVIORAL THERAPY (CBT) DALAM PROSES PEMULIHAN KESEHATAN MENTAL WARGA BINAAN PEMASYARAKATAN (WBP) DI LAPAS NARKOTIKA KELAS IIA BANDAR LAMPUNG - Aldinan, Ripaldo; mubasit, mubasit; Noffiyanti, Noffiyanti (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2026)
This study aims to examine the implementation of individual counseling using the Cognitive Behavioral Therapy (CBT) approach in the process of mental health recovery among inmates at the Class IIA Narcotics Correctional Institution in Bandar Lampung. The background of this research is based on the high prevalence of mental health disorders among inmates, influenced by the pressures of the correctional environment, past life experiences, and limited social support. This study employs a qualitative approach with a descriptive field research design. The research subjects consist of one counselor and four inmates selected through purposive sampling. Data collection techniques include non-participant observation, unstructured interviews, and documentation, while data analysis uses the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that the implementation of CBT in individual counseling is carried out through several stages, namely initial assessment, psychoeducation, and intervention. At the assessment stage, inmates generally experience anxiety, stress, and difficulties in adapting. The psychoeducation stage helps inmates understand the relationship between thoughts, emotions, and behaviors, thereby increasing self-awareness. Meanwhile, at the intervention stage, techniques such as cognitive restructuring, self-talk, and relaxation are proven to help inmates transform negative thinking patterns into more rational ones and improve emotional control and adaptive behavior. Observational findings also indicate positive changes among inmates, including improved emotional regulation, better social interactions, and increased participation in rehabilitation activities. The conclusion of this study indicates that CBT-based individual counseling is effective in supporting inmates’ mental health recovery. This approach not only reduces levels of anxiety and depression but also enhances self-control, positive thinking patterns, and readiness for rehabilitation and social reintegration. Therefore, CBT is recommended to be implemented systematically and sustainably within correctional institution rehabilitation programs.